2001
DOI: 10.1136/gut.49.4.534
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the staging performance of endoscopic ultrasound in gastro-oesophageal carcinoma

Abstract: Background-EndoscopicIn articles that compared EUS directly with incremental computed tomography, EUS performed better. None of the variables assessed in the regression analysis was significant using a Bonferroni correction. Three variables (anatomical location, traversability, and blinding) showed strong relationships for future research and validation. Conclusions-EUS is highly eVective for discrimination of stages T1 and T2 from stages T3 and T4 for primary gastrooesophageal carcinomas. The failure rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
198
3
7

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 338 publications
(214 citation statements)
references
References 41 publications
6
198
3
7
Order By: Relevance
“…There are few other published systematic reviews and meta-analyses assessing EUS performance for staging gastric cancer. An early systematic review by Kelly et al [5] evaluated 27 articles, published between 1981 and 1996, of which 13 evaluated gastric cancer, and found that EUS performed better for staging gastric carcinoma compared to carcinomas of the esophagus. As with the study by Kelly et al, we found that EUS performed better when staging tumor invasion than when staging nodal status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few other published systematic reviews and meta-analyses assessing EUS performance for staging gastric cancer. An early systematic review by Kelly et al [5] evaluated 27 articles, published between 1981 and 1996, of which 13 evaluated gastric cancer, and found that EUS performed better for staging gastric carcinoma compared to carcinomas of the esophagus. As with the study by Kelly et al, we found that EUS performed better when staging tumor invasion than when staging nodal status.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic ultrasound (EUS) was introduced into clinical practice in the early 1980s as a way to assess the extent of local tumor infiltration and local lymph node status [5][6][7]. The main advantage of EUS is the ability to place the transducer close to the lesion without interference of fat, bowel gas, or bone [6].…”
Section: Endoscopic Ultrasoundmentioning
confidence: 99%
“…EUS has been used widely as a powerful means of assessing clinical T and N status, with some studies reporting that EUS is superior to CT for evaluating regional LN metastasis and a diagnostic accuracy for LN involvement of approximately 80% (37)(38)(39)(40). However, other studies found that EUS tended to overestimate LN involvement and that the EUS accuracy was operator-dependent due to the experience required to master the technique (21,41,42).…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…In addition, the inability of EUS to clearly distinguish between the adventitial and the subadventitial layer is another source of error in the differentiation of T2 tumors that deeply infiltrate into the subadventia and T3 carcinomas. [16][17][18] Our study has several limitations. Our data contains a narrow clinical spectrum of diseases, with patients who had T1 or T2 stage in 73%.…”
Section: Discussionmentioning
confidence: 99%